1990
DOI: 10.1007/bf00916568
|View full text |Cite
|
Sign up to set email alerts
|

Early antecedents of childhood impulsivity: The role of parent-child interaction, cognitive competence, and temperament

Abstract: This prospective longitudinal investigation examined early mother-child interaction as a predictor of childrenThe emergence of self-regulation is one of the most significant developmental landmarks of the early childhood period

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
132
2
6

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 173 publications
(150 citation statements)
references
References 32 publications
10
132
2
6
Order By: Relevance
“…In particular, clear, consistent limit setting in the presence of noncompliance and scaffolding of children's behaviors, that is, responsiveness to negative affect together with facilitation of child autonomy, predicted relative increases in effortful control. Although previous studies have shown that sensitive, warm, and responsive parenting predict the development of self-regulation (Block & Block, 1980;Olson et al, 1990;Kochanska et al, 2000;Eisenberg, Zhou, et al, 2003) these maternal behaviors were not examined independently of other aspects of parenting such as limit setting and scaffolding. In addition, variables labeled as sensitivity might share aspects of limit setting and scaffolding as assessed in this study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, clear, consistent limit setting in the presence of noncompliance and scaffolding of children's behaviors, that is, responsiveness to negative affect together with facilitation of child autonomy, predicted relative increases in effortful control. Although previous studies have shown that sensitive, warm, and responsive parenting predict the development of self-regulation (Block & Block, 1980;Olson et al, 1990;Kochanska et al, 2000;Eisenberg, Zhou, et al, 2003) these maternal behaviors were not examined independently of other aspects of parenting such as limit setting and scaffolding. In addition, variables labeled as sensitivity might share aspects of limit setting and scaffolding as assessed in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Measures of adaptive, sensitive, or warm parenting have been shown to predict effortful control (Eisenberg, Zhou et al, 2003) and related constructs such as ego-control (Block & Block, 1980) and impulsivity (Olson, Bates, & Bayles, 1990). Maternal responsiveness when children were 22 months old predicted the development of effortful control from 22-to 33-months (Kochanska et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Given that children with behavior concerns elicit increased direction and control from adults (Olson, Bates, & Bayles, 1990;Winsler, 1998), teachers may unnecessarily ask children to be quiet in classrooms out of fear that such speech coming from difficult-to-manage children will lead to problem behavior. Teacher training and professional development efforts could thus focus on helping teachers avoid such a conclusion and suggest that teachers increase their tolerance level for children's non-disruptive overt private speech use in the classroom.…”
Section: Discussionmentioning
confidence: 99%
“…Empirical studies on this topic have also highlighted the role of maternal warmth, sensitivity, and disciplinary strategies as predictors of self-regulation (e.g., Eisenberg, Cumberland, & Spinrad, 1998;Eisenberg et al, 2001Eisenberg et al, , 2003Emde, Biringen, Clyman, & Oppenheim, 1991;Olson, Bates, & Bayles, 1990). Children with warm, sensitive parents are more likely to be …”
Section: Parentingmentioning
confidence: 99%